2006
DOI: 10.5465/amle.2006.22697018
|View full text |Cite
|
Sign up to set email alerts
|

Academic Dishonesty in Graduate Business Programs: Prevalence, Causes, and Proposed Action

Abstract: Little is currently known about cheating among graduate business students. We collected data from more than 5,000 business (mostly MBA) and nonbusiness graduate students at 32 colleges and universities in the United States and Canada during the 2002-2003 and 2003-2004 academic years to test a series of hypotheses regarding the prevalence of graduate business student cheating and reasons why these students cheat. We found that graduate business students cheat more than their nonbusiness-student peers. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
339
0
24

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(395 citation statements)
references
References 21 publications
12
339
0
24
Order By: Relevance
“…The presumption would be that some noble courses like Medicine and Engineering that deal with matters of life and death would be free of the finding that only 55.8% of medical students are truthful; just slightly better than tossing a coin on whom to believe! One would be tempted to augment this finding with the fact that the participation level of 60.9% is perfectly within study findings of a range 13-95% for the others 1 and made more colourful by an awareness of 80% and witnessing of the vice in progress at 75.6%. It is possible that the trends on academic dishonesty are no respecters of any given profession and this might explain why we are increasingly getting litigations aimed at respected professions like Medicine and Architecture 9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presumption would be that some noble courses like Medicine and Engineering that deal with matters of life and death would be free of the finding that only 55.8% of medical students are truthful; just slightly better than tossing a coin on whom to believe! One would be tempted to augment this finding with the fact that the participation level of 60.9% is perfectly within study findings of a range 13-95% for the others 1 and made more colourful by an awareness of 80% and witnessing of the vice in progress at 75.6%. It is possible that the trends on academic dishonesty are no respecters of any given profession and this might explain why we are increasingly getting litigations aimed at respected professions like Medicine and Architecture 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies done on academic dishonesty have all along been counting on the honesty and truthfulness of the respondents while at the same time exploring on a vice acknowledged to be complex and widespread [1][2][3][4] . We now have a situation where students consider dishonesty as a way of life "because everybody does it" 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We caution that this finding not be taken to suggest that fear of punishment has no impact: Indeed, there is a wealth of evidence to suggest that punishment does in fact deter students from cheating (Cizek, 1999). Rather than fear per se, it may be that perceived likelihood of being turned in by a peer is the psychological mediator (McCabe et al, 2006).…”
Section: Explaining the Psychopathy-cheating Linkmentioning
confidence: 99%
“…Watson et al presented a case study of the in-class use of a video game for teaching high school history [21]. However, the use of technology may have negative impact [22][23][24][25]. Bray and Tangney [6] conducted a study to evaluate the impact of using mobile technologies in students' engagement; they found that the use of mobile technologies increases student engagement.…”
Section: Introductionmentioning
confidence: 99%